Investing in risky inputs in Senegal: Implications for farm profit and food production - Anatole Goundan; Amy Faye; Christian H. C. A. Henning; Peron A. Collins-Sowah (Kiel University, Department of Agricultural Economics, Chair of Agricultural Policy, 2020)
While the productivity effects of the application of modern inputs, such as im- proved seeds or inorganic fertilizer, are well known, farmers in Sub-Saharan Africa tended to underinvest in purchased inputs. This underinvestment appears related to the unpredictable nature of agricultural production that is subject to risks and shocks. Farmers make production decisions before climatic and other shocks are realized. They, therefore, have no certainty about the outcome of their decisions. This makes investments in agricultural inputs very risky. This paper uses recent data for Senegal to identify the main drivers of the decision to purchase risky inputs (seeds and/or fertilizers), the level of investment and to quantify the impact of the use of risky inputs on household welfare. Using a Heck- man model, results show that the main drivers of the decision to purchase risky inputs include household composition, farmer organization, farm size, access to livestock income, and crop diversification. Drivers of the level of investment in risky inputs are gender, extension services, farm size, agricultural capital, and cropping patterns. Using an endogenous switching regression, we find a positive impact on the adoption of risky inputs on farm profit per hectare, and food available from production. The expected impact for non-adopters is found to be higher than that for adopters because they are involved in rice production (which is more responsive to inputs use) and in millet production (which is central for food security).
urn:nbn:de:gbv:8:3-2021-00193-1
Keywords: 330; Risky inputs; purchased fertilizers; purchased seeds; household welfare; Senegal